Finite element parametric study on the cyclic response of steel frames equipped with comb-teeth dampers. (June 2021) - Montazeri, Ehsan; Kazemi, Seyed Morteza; Askariani, Seyed Saeed
Abstract: Comb-Teeth dampers (CTDs) are a new type of metallic yielding dampers developed for passive control of structures. These dampers are installed between the floor beam and chevron braces in steel frames. They are made up of identical teeth combined in parallel with each other during loading and dissipate the input energy by in-plane plastic deformations. Experiments and numerical simulations have verified the effectiveness of CTDs as an energy dissipation device in structures. However, a comprehensive parametric study has not yet been performed on the behavior of these dampers. The parametric study provides exciting findings that could guide the future design of frames equipped with CTDs. This paper presents a comprehensive numerical parametric study on the cyclic response of single-story single-bay steel frames equipped with CTDs. Numerical modeling is validated using the results of an experimental study. The studied parameters are end fillet radius, thickness, geometric shape coefficient, and height of damper teeth. The results show that all the studied parameters can considerably affect all the behavioral characteristics of the frame.